AUTHENTIC LEADERSHIP BEHAVIOR IN PUBLIC MIDDLE SCHOOL - Johansyah, Johansyah (Universitas Pendidikan Indonesia, 2022)
This study aims to determine the effect of managerial competence and cooperation of school principals on the job satisfaction of educators in state junior high schools in East Borneo. This research uses quantitative and descriptive approaches. In terms of this type of research is a type of correlational research that is research that seeks to connect two or more variables based on facts that have occurred through data collection, data processing, then analyzing and finally explaining according to facts. The population of this study was all school principals and state junior high school teachers in East Borneo (South Balikpapan and East Kutai). The sampling technique uses this purposive sampling technique by taking schools in the Municipality of Balikpapan and East Kutai with a total of 20 teachers. The results of this study indicate that there is a positive and significant correlation between the managerial skills of school principals ((X1) and the satisfaction of teachers (Y) of SMP in East Borneo with a partial correlation coefficient of 0.450. then known that there is a significant correlation between the cooperation of principals (X2) on the satisfaction of teaching staff (Y) SMP in East Borneo with a partial correlation coefficient of 0.209. and there is a significant influence between the managerial skills of principals (X1) and collaboration of principals (X2) on the satisfaction of educators (Y) Middle East Borneo Middle Schools with a multiple correlation coefficient (Multiple R) of 0.440 which means that the managerial skills of principals ((X1) and the cooperation of school principals (X2) towards the satisfaction of educators (Y) is 44.0% so that the high and low level of managerial skills in school principals, and the cooperation of school principals will determine the satisfaction of teacher performance.This study aims to determine the effect of managerial competence and cooperation of school principals on the job satisfaction of educators in state junior high schools in East Borneo.[MOU1] This research uses quantitative and descriptive approaches[MOU2] . In terms of this type of research is a type of correlational research that is research that seeks to connect two or more variables based on facts that have occurred through data collection, data processing, then analyzing and finally explaining according to facts. The population of this study was all school principals and state junior high school teachers in East Borneo (South Balikpapan and East Kutai). The sampling technique uses this purposive sampling technique by taking schools in the Municipality of Balikpapan and East Kutai with a total of 20 teachers. The results of this study indicate that there is a positive and significant correlation between the managerial skills of school principals ((X1) and the satisfaction of teachers (Y) of SMP in East Borneo with a partial correlation coefficient of 0.450. then known that there is a significant correlation between the cooperation of principals (X2) on the satisfaction of teaching staff (Y) SMP in East Borneo with a partial correlation coefficient of 0.209. and there is a significant influence between the managerial skills of principals (X1) and collaboration of principals (X2) on the satisfaction of educators (Y) Middle East Borneo Middle Schools with a multiple correlation coefficient (Multiple R) of 0.440 which means that the managerial skills of principals ((X1) and the cooperation of school principals (X2) towards the satisfaction of educators (Y) is 44.0% so that the high and low level of managerial skills in school principals, and the cooperation of school principals will determine the satisfaction of teacher performance. [MOU1]don't need to be listed [MOU2]should be: This research uses Descriptive method and quantitative approach.